The Influence of Different Treatment Strategies on the Long-Term Prognosis of T1 Stage Esophageal Cancer Patients - Pan, Liang; Liu, Xingyu; Wang, Weidong; Zhu, Linhai; Yu, Wenfeng; Lv, Wang; Hu, Jian (Frontiers in Oncology, 2021)
Objective To compare the long-term prognosis effects of non-esophagectomy and esophagectomy on patients with T1 stage esophageal cancer. Methods All esophageal cancer patients in the study were included from the National Surveillance Epidemiology and End Results (SEER) database between 2005-2015. These patients were classified into non-esophagectomy group and esophagectomy group according to therapy methods and were compared in terms of esophagus cancer specific survival (ECSS) and overall survival (OS) rates. Results A total of 591 patients with T1 stage esophageal cancer were enrolled in this study, including 212 non-esophagectomy patients and 111 esophagectomy patients in the T1a subgroup and 37 non-esophagectomy patients and 140 esophagectomy patients in the T1b subgroup. In all T1 stage esophageal cancer patients, there was no difference in the effect of non-esophagectomy and esophagectomy on postoperative OS, but postoperative ECSS in patients treated with non-esophagectomy was significantly better than those treated with esophagectomy. Cox proportional hazards regression model analysis showed that the risk factors affecting ECSS included race, primary site, tumor size, grade, and AJCC stage but factors affecting OS only include tumor size, grade, and AJCC stage in T1 stage patients. In the subgroup analysis, there was no difference in either ECSS or OS between the non-esophagectomy group and the esophagectomy group in T1a patients. However, in T1b patients, the OS after esophagectomy was considerably better than that of non-esophagectomy. Conclusions Non-esophagectomy, including a variety of non-invasive procedures, is a safe and available option for patients with T1a stage esophageal cancer. For some T1b esophageal cancer patients, esophagectomy cannot be replaced at present due to its diagnostic and therapeutic effect on lymph node metastasis.